China's overseas investment in critical infrastructure: Nuclear power and telecommunications - Yang Jiang; Aki Tonami; Adam Moe Fejerskov (Danish Institute for International Studies (DIIS), 2016)
China's interest in other countries' infrastructure has become a sensitive issue for governments and media, in particular in Western countries. In particular, Chinese companies are aggressively seeking entrance into the European market, and European countries may find Chinese companies to be the only serious bidders for expensive, low-profit and long-term infrastructure projects. Many countries have procedures for reviewing intentions of foreign investment in their critical infrastructure, defined as infrastructure that is closely related to issues of sovereignty and national security. This new DIIS Defence and Security Studies Policy Report provides an overview of how various countries have received Chinese interests in investing in their critical infrastructure, using the examples of the nuclear power and telecommunication industries. In the view of host country governments, Chinese investment in nuclear and telecommunications infrastructures may have consequences for nuclear security and safety and information security respectively. For nuclear power and uranium mining, the report reviews the latest Chinese investments (planned or realised) in the UK, Greenland, Pakistan, the Middle East and Ukraine. For telecommunications, the report analyses the wide range of responses from countries - the Scandinavian countries, US, UK and selected African countries. In a nutshell, host country attitudes and policies towards Chinese investment in telecommunications and nuclear power vary widely. Some countries reject Chinese investment in these areas because of distrust in Chinese companies based on their perceived connection to the Chinese government, and others have accepted them due to economic needs and diplomatic relations with Beijing, and put into place various review and monitoring mechanisms. Moreover, Chinese investors may not be more risky than those from other countries, including Western investors. Based on the empirical cases, the report discusses the implications for national and international security, and comes up with policy recommendations for Denmark.
Keywords: 300